Enhancing the quality of life of drug addicts: The role of social support - Dzulkifli, Mariam Adawiah; Mohamad, Mardiana; Abdul Rahman, Wan Rafaei; Sheikh Dawood, Shariffah Rahah (2011)

(untitled)
Drug addiction is a very serious issue facing by the world population.The January-December 2008 National Drug Information System Unit (NADI) report indicated that the Malaysian drug situation remains a serious one.The data from Agensi Antidadah Kebangsaan (2007) shows an increase in the number of drug abuse and relapse cases among Malays in Malaysia and one of the factors that has been linked to drug addiction and relapse cases is the lack of social support